2022
DOI: 10.1155/2022/8760615
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Effect of Platelet-to-Lymphocyte Ratio in Predicting Cardiovascular Mortality of Peritoneal Dialysis Patients

Abstract: Background. The study is aimed at exploring the relationship of platelet-to-lymphocyte (PLR), all-cause, and cardiovascular disease (CVD) mortality in peritoneal dialysis (PD) patients based on gender. Methods. A total of 1438 PD patients from January 1,2007 to December 31, 2014 in PD center at The First Affiliated Hospital, Sun Yat-sen University, were included. Patients were followed up until December 31, 2019. The endpoint was all-cause mortality and CVD mortality. Cox proportional hazards regression models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Huang et al reported the effect of different gender on PLR ratio to predict cardiovascular mortality of peritoneal dialysis (PD) patients. For female PD patients, high PLR ratio was related to worse prognosis due to higher level of estrogen and low levels of serum iron 33 . Our study did not find the same effect of gender in our TBI patients.…”
Section: Discussionmentioning
confidence: 97%
“…Huang et al reported the effect of different gender on PLR ratio to predict cardiovascular mortality of peritoneal dialysis (PD) patients. For female PD patients, high PLR ratio was related to worse prognosis due to higher level of estrogen and low levels of serum iron 33 . Our study did not find the same effect of gender in our TBI patients.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have indicated that there have been similar biological biomarkers verified to predict mortality in PD patients, such as NLR, PLR, MLR and LHR. [36][37][38][39] In the current study, we compare the predictive values of NPAR with NLR, PLR, MLR and LHR. Our findings revealed that NPAR had a higher AUC value compared with other four biomarkers and showed superior and more reliable predictive efficiency.…”
Section: Dovepressmentioning
confidence: 99%
“…In dialysis and non-dialysis patients with chronic kidney disease(CKD), PLR has been reported to be associated with inflammation [ 16 ]. And some studies also have shown that PLR is associated with all-cause mortality and the prognosis of cardiovascular events in patients with CKD [ 16 19 ]. To date, no studies have revealed the association between PLR and PDRP in PD patients.…”
Section: Introductionmentioning
confidence: 99%